A Comprehensive Overview on Microalgal-Fortified/Based Food and Beverages. Issue 8 (17th November 2019) - Sidari, Rossana; Tofalo, Rosanna
ABSTRACT: Microalgae produce a variety of compounds that can be used for aquaculture, nutraceutical purposes, and third-generation biofuel sectors. Moreover, they have been considered for the production of fortified food and beverages claiming to be healthier than other foods. Using microalgal oil or incorporating microalgae biomass or their metabolites in food and beverages provides health benefits due to properties such as anti-inflammatory, antioxidant, immune-enhancing, and to their role against various diseases such as cardiovascular metabolic, atherosclerosis, and hypertension. This review focuses on the worldwide research carried out about the incorporation of microalgae – either biomass or their high-value compounds – in food and beverages, and on the microalgal fortified/based food and beverages currently present worldwide on the market. The metabolites bioavailability aspect and the current legislation are considered. There is an ever-growing interest in this field but the volume of production is still limited. Various challenges, one of which is the cost of producing biomass, need to be overcome for a profitable market. More effort, involving different expertise, is needed to improve the microalgal production system, from cultivation to harvesting and biorefinery, to produce improved novel products.